1984
DOI: 10.2135/cropsci1984.0011183x002400040029x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Habit of Beans on Tolerance to Competition from Maize When Intercropped1

Abstract: Three trials were planted at CIAT, Colombia, with selected lines of red seeded beans (Phaseolus vulgaris L.), representing the best that has emerged from breeding of each growth habit, in order to study the relationship between growth habit and competitive ability with maize (Zea mays L.) when intercropped. Treatments included sole cropping without stakes, and with stakes that varied in height from 1 m to 2 m, and intercropping with short and tall maize cultivars. Highly significant interactions of bean lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This is supported by the finding that in intercropping studies which involve different cultivars of the same crop, a significant genotype by cropping system interaction occurs, demonstrating that intercropping systems favour more genotypes that perform poorly as sole crops rather than the highly performing when grown alone (Davis et al 1984;Tsay et al 1988;Santalla et al 2001;Tefera and Tana 2002;Hauggaard-Nielsen and Jenssen 2001;Atuahene-Amankwa et al 2004;O'Leary and Smith 2004;Gebeyehu et al 2006).…”
Section: Stand Uniformity and Productivitymentioning
confidence: 82%
See 1 more Smart Citation
“…This is supported by the finding that in intercropping studies which involve different cultivars of the same crop, a significant genotype by cropping system interaction occurs, demonstrating that intercropping systems favour more genotypes that perform poorly as sole crops rather than the highly performing when grown alone (Davis et al 1984;Tsay et al 1988;Santalla et al 2001;Tefera and Tana 2002;Hauggaard-Nielsen and Jenssen 2001;Atuahene-Amankwa et al 2004;O'Leary and Smith 2004;Gebeyehu et al 2006).…”
Section: Stand Uniformity and Productivitymentioning
confidence: 82%
“…The major reason is the unequal share of resources in the presence of competition, that the growth and the development of individuals are suppressed unevenly Fasoula 1997a, 2002;Fasoula and Tollenaar 2005). A particular cause also is the competition's connection with decreased harvest index due to inefficient resource use, as was documented in bean and wheat genotypes (Davis et al 1984;Pan et al 2003;Gebeyehu et al 2006). Pan et al (2003) pointed out that greater plant size hierarchy induced by competition implies a high incidence of growth redundancy which is detrimental to the yield performance of a crop population.…”
Section: Stand Uniformity and Productivitymentioning
confidence: 99%
“…Decades of intercropping research have demonstrated that cereals are usually the dominant component in cereal–legume mixtures, suppressing the growth of the legume and contributing a greater proportion of biomass to the total mixture yield (Ofori and Stern, 1987). This competitive imbalance may be more severe for low‐growing legumes than for those with climbing growth habits (Davis et al, 1984; Fukai and Trenbath, 1993), but the performance of vetch in mixture with cereals still varies across studies. Kurdali et al (1996) and Tosti et al (2010) both saw reduced vetch dry matter productivity in a mixture with barley ( Hordeum vulgare L.), while Dhima et al (2007) also observed suppression of vetch by barley and oat ( Avena sativa L.) but not by wheat ( Triticum aestivum L.) or triticale (× Triticosecale Wittmack).…”
Section: Resultsmentioning
confidence: 99%
“…The author suggested that this may be due to competition for light. (See CIAT [1980] or Davis et al [1984] for descriptions of growth habit types in beans.) Total weed growth was higher in 'Tara' plots (2560 vs. 2480 kg/ha for 'Great Northern 1140'); however, 'Tara' outyielded 'Great Northern 1140' under weed-free and weedy conditions.…”
Section: Common Bean (Phaseolus Vulgaris)mentioning
confidence: 99%